Liquid-liquid phase separation: an emerging perspective on the tumorigenesis, progression, and treatment of tumors - Jian, Qin; Xu, Qi; Xiang, Sirui; Wang, Rongrong; Wang, Chuchu; Zhang, Boxun; Li, Ruli; Lin, Junzhi; Zheng, Chuan (Frontiers in Immunology, 2025)
Research in the field of Liquid-liquid phase separation (LLPS) breaks through the classical theory of gene mutation in the mechanism of tumorigenesis and provides a new perspective for comprehending tumors from a network regulation standpoint. Although there have been some reviews discussing the relationship between LLPS and tumors, they often focus on elaborating isolated mechanisms. In the face of complex and diverse disease characteristics, it is necessary to summarize the correlation between LLPS and tumors through a linked and holistic approach to reveal the deep-rooted relationships among tumor disease mechanisms. Therefore, we adopt a dual-dimensional analytical framework, where one dimension (the longitude) integrates cellular physiology, tumorigenesis, progression, and therapeutic responses, while the other dimension (the latitude) focuses on the pathogenic characteristics of tumors. This structural design enables comprehensive analysis of LLPS functions across both dynamic processes and pathological features. This article first outlines how LLPS regulates normal cellular physiological activities, such as gene expression, DNA damage response (DDR), and epigenetic modifications. It then summarizes how LLPS malfunction promotes tumorigenesis and progression, including the oncogenic processes of fusion oncoproteins (FOs) expression, tumor suppressor gene mutation, epigenetic modification defect, and DDR repair abnormality, as well as the tumor progression processes of proliferation and metastasis, dysregulation of autophagy, and metabolic reprogramming. Promising therapeutic strategies are then proposed. Finally, the existing research is prospected. The above insights drive the innovation of LLPS-based tumor therapeutic strategies and the development of targeted antitumor drugs.